PENERIMAAN E-WALLET SYARIAH LINKAJA DALAM RANGKA PENGEMBANGAN EKONOMI DIGITAL DI INDONESIA - Irma Andriyaningtyas; Muhammad Adam; Sri Herianingrum (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
The emergence of sharia-based E-Wallet is a new thing in Indonesia and an academic response is needed for this. This article is intended to measure the level of individual acceptance of Sharia E-Wallet by looking at the relationship between factors related to intention, by using modification and simplification of the UTAUT model and using the analysis of Structural Equation Modeling (SEM) analysis. This study found that factors such as User Value, Effort Expectancy and Social Influence have a positive and significant impact on Performance Expectancy. In the context Behavioral Intention relationship it is found that there is a positive and significant influence between Effort Expectancy and Social Influence on the Intention to adopt Sharia E-Wallet. Meanwhile, User Value and Performance Expectations do not have a significant and positive relationship. This research provides advice in building a digital economy in Indonesia through a program of strengthening Literacy and Regulation in utilizing the potential of Muslims and preferences in using sharia products in Indonesia in accordance with the grand plans in Building Sharia Economic and Finance 2019-2024.